Social Media in the LINC Classroom: Instructors’ Perceptions, Barriers and Support Necessary for Effective Integration - Zekri, Ibtissem (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2021)
The use of social media (SM) platforms in the Language Instruction for Newcomers to Canada (LINC) program has remained under examined compared to other contexts. The goal of this mixed-method study is to fill this gap by investigating LINC instructors’ perceptions about SM integration in English language learning, the barriers that might hinder such integration and the support needed to make it more effective. The findings, which have implications for policymakers and LINC programs administrators, suggest that LINC instructors have positive perceptions about using SM in English language learning. However, removing existing barriers is a prerequisite to a successful SM integration.